The impact of the Ease Doing Business Indicators on Foreign Direct Investment in the European transition economies - Haliti, Bersan; Merovci, Safet; SHERPA, Sanjib; Hetemi, Alban (Ekonomika, 2020)
The objective (aim) of this paper is to explore the impact of the Ease of Doing Business Indicators on FDI on transition economies in Europe. Authors have used the dynamic panel methodology, by using three methods: Pooled Ordinary Least Square (POLS), Fixed Effect (FE), and Two Step-System Generalised Method of Moments (GMM) estimation techniques. By referring to the GMM technique, it can be seen that variables such as: Starting a Business, Registering property, Getting electricity and Resolving insolvency have a positive and significant impact in attracting FDI in 16 European transition countries, while variables as: Dealing with construction permits, Getting credit, Paying taxes, Protecting minority investors, have shown negative impact, whereas Trading Across Border and Enforcing contracts have not shown any impact on attracting FDIs in European transition countries. This paper contributes to the enrichment of existing literature in this field by using these three methods.
Keywords: FDI; Ease of Doing Business Indicators; Transition economies